The Influence of The #Pilahsampah Campaign on Instagram on The Intention of Sorting Plastic Waste in Youth - Raymon Godwin; Clara Verena; Cornelia Instiani (Bina Nusantara University, 2023)
Research looks at the effect of the #pilahsampah campaign on Instagram on the intention to sort plastic waste in adolescents. The #pilahsampah campaign includes information on Instagram media about waste sorting. Experimental design study with 74 adolescent participants from DKI Jakarta with an age range of 19-23 years. Intention to sort waste was measured using a questionnaire developed by researchers based on the ATCT intention criteria theory (Action, target, context, and time) by Fishbein and Ajzen (2005). The results based on the analysis of the Independent T-test showed that in the post-test of the experimental group there were differences from the pre-test that was done previously compared to the control group (Sig.=0.00, p-value <0.05). It was concluded that the #pilahsampah campaign on Instagram had a significant influence on the intention to sort plastic waste among teenagers.